Evaluation of some Limiting Factors affecting Water chlorination at Baghdad / Al-Kurch District - Najim, Najim Hadi; Aziz, Rebwar Tahir (The Iraqi Journal of Veterinary Medicine, 2012)
This study was designed to high light about the effect of some factors individually or in combination that shared in the reduction of the chlorine activity and efficiency for meeting the bacterial standards as a disinfection agent for drinking water at Baghdad city/ Al- kurch. To achieve the objectives (137) drinking water samples were collected from July up to the end of November 2007 from the houses of Baghdad's citizens/ Al-kurch. Also studying the scientific nature of some municipal water supply at Baghdad/ Al- kurch, drinking water samples were collected from faucets after allowing the water to run for 0, 5 and 10 minutes. Statistical data showed that there was non significant difference in both the chlorine concentration and coliform counts in all samples that were taken after allowing the water to run for 0, 5 and 10 minutes and for that reason drinking water samples after allowing the water to run for 5 minutes were chosen as the best time for sampling in this research.Data revealed that the free chlorine in drinking water was below the standards set by the World Health Organization (WHO) in the period from July up to the end of August 2007, whereas the highest Coliform counts in drinking water were established during the above mentioned months, while the coliform counts decreased in the period from September up to the end of November 2007 due to the utilization of higher concentrations of total chlorine in drinking water in municipal water supply, in addition to that, the effect of some variables such as quantity of free chlorine, temperature, pH and oxidation- reduction potential of water on the sanitizing efficiency of the chlorine were studied.The statistical data revealed that there was a significant negative correlation (P < 0.01, r = -0.072) between the chlorine sanitizing efficiency with both the concentration of the free chlorine and its contact time with microorganisms while the effect of temperature, pH and oxidation- reduction potential of water showed non significant effect on the chlorine sanitizing efficiency.